A atuação dos comitês de auditoria e conselhos fiscais nas empresas brasileiras sujeitas à regulamentação da SEC - Securities and Exchange Commission dos Estados Unidos da América - Almeida, Cesar de Alencar Leme de (2008)
More and more, Brazilian companies have offered their securities to the investment public at international stock exchanges, especially the New York Stock Exchange. However, financially attractive to issuers as compared to other fund-raising sources, a public offering abroad calls for compliance with other regulatory requirements. In the case of the US, the financial scandals publicized early in this decade led to changes in money market regulations, with more stringent requirements on listed companies. Among the various requirements then imposed is the strengthening of Audit Committees for improvement of Corporate Governance practices. Because Audit Committees are not legally required under the Brazilian corporate legislation, the Brazilian Securities Commission (CVM) together with authorities from other countries which do not have such commission agreed with the Securities & Exchange Commission SEC to replace Audit Committees with similar agencies; e.g., the Fiscal Council, in the case of Brazil. According to the SEC, as it is independent of the Administrative Council, the Fiscal Council might perform an Audit Committee s functions, providing that some of the latter s attributions are also taken over. Against this background, there are currently two groups of Brazilian, non-financial companies listed in the New York Stock Exchange, namely: one which voluntarily formed its Audit Committee, and one which maintained its Fiscal Council with expanded functions, now known as "Conselho Fiscal Turbinado" (Powered Fiscal Council). The study was primarily designed to identify the Brazilian companies listed at the NYSE New York Stock Exchange, and among them, those which formed their Audit Committee and those which maintained their Fiscal Council. A bibliographic survey was conducted to identify the differences between the Brazilian and the US capital markets, the attributions assigned to Audit Committees, and their compliance with the respective agencies´ Internal Regulations. Thus, it was possible to check for compliance with these attributions and the similarity of functions established by the Audit Committees and Fiscal Councils researched. The research findings prove that the attributions of these two agencies are homogeneous. Lastly, possible new academic studies on this subject are presented